Building a Movement Through Partnerships and Public Engagement:One Organization, Many Communities, and a Landfill - Guzenski, Nicole (My University, 2018)
This reflective paper will explain and summarize a community engagement capstone project focused on building a partnership with Friends of Lackawanna (FOL), an organization that has been developed in order to oppose a 50 year expansion proposed by the Keystone Sanitary Landfill (KSL) in Dunmore and Throop, Pennsylvania. The expansion would add about 106 million tons of waste to the landfill’s capacity, making the physical height of the landfill about 220 feet higher than its current height. Local residents have expressed concerned over the landfill’s traffic, pollution, effects on air quality, and the overall impacts to the health of residents and the environment. The capstone project’s mission was to develop more opportunities for the Friends of Lackawanna to engage the community around the topic of waste, the environment, and the issue of the landfill while also increasing the organization’s outreach. This paper outlines, reflects, and analyzes the methods of engagement used to create social awareness around the issues within the context representative of the organization’s (FOL) commitment to community organizing. The project worked to incorporate various ways to use public engagement tied to the proposed expansion of the KSL landfill such as a children’s art exhibit, engaging youth to act as leaders by sharing their stories and creating art as part of a local workshop, and an outdoor, environmentally focused fair. The project explored ways to implement and increase tools or strategies for FOL in order to engage deeper with community members by demonstrating the importance of partnerships and the development of social networks. Throughout this project I discovered various ways that FOL can work to increase visibility and support through active governance and stewardship with community by reviewing their community engagement efforts and partnerships with local residents, organizations, and agencies. I also developed an organizational history and timeline of indicators of FOL’s work. This helped the project determine recommendations that align with the organization’s mission and aid in the progress of the achieving their goals. The organizational history helped in demonstrating ways that community members have engaged or needed to engage with the organization and determine what roles FOL plays within the community. My reflective responses and collections are documented through photographs and an Internet based, password protected, blog. The purpose of the blog was to serve as ongoing journal to store experiences, stories, reflections, ideas, and photographs. It also serves as a way to demonstrate the various partnerships which were created to plan public events and local activities, which were an integral part of this project. The blog contains outside links to organizations, partners, and events in order to showcase local collaborations which supported the project’s work. The blog was also created to serve the Cultural Sustainability community and its students, so that they will be able see and read what a capstone project entails in order to provide guidance and to improve upon the uses and implementation of a graduate project for their community and future work.
The blog can be accessed at: https://niguz001.wixsite.com/capstone All pages are password protected using the password (all caps): MACS Additional photographs can be found on the blog, along with reflective writings and links to partnership websites.
Keywords: environmentalism; cultural sustainability; community organizing; environmental sustainability; art and activism; public engagement; social movements; Environmental Justice; community building; partnerships; Cultural sustainability -- Capstone (Graduate)